Edukasi Gizi Pengaturan Pola Makan dan Gizi Seimbang Untuk Pencegahan Gangguan Menstruasi Pada Remaja di SMA 10 Bontoramba Kab Jeneponto - Irmawati.S; Rosdianah Rosdianah; Syamsur Yanita; Nurul Ikawati (jurnal ABDIMAS Indonesia, 2024)
Dysmenorrhea is pain in the lower abdomen that occurs before or during menstruation, often accompanied by symptoms such as sweating, headache, nausea, vomiting, and shaking. The negative impacts of primary dysmenorrhea in teenagers are academic decline, loss of concentration, and not attending class. One of the causes of dysmenorrhea is lack of knowledge about the cause of menstrual disorders such as unbalanced nutritional intake. The solution to increase this knowledge is by providing nutrition education about balanced diet and nutrition. All community partnership program activities consisting of counseling, discussion, and evaluation which are conducted online. The measurement of success was carried out by distributing a pre-posttest questionnaire about knowledge of balanced diet and nutrition using the google form. The results of the pretest showed that only 22% of teenagers had good knowledge. After being given education, it showed an increase in knowledge of 75%.